Nitrogen side-dress as a strategy to reduce defoliation demages at different growth stages of maize - Sangoi, Luis; Picoli Junior, Gilmar José; Vargas, Vitor Paulo; Vieira, Jefferson; Schmitt, Amauri; Zoldan, Sérgio Roberto; Siega, Eduardo; Carniel, Giovani (Semina: Ciências Agrárias, 2014)
Nitrogen can mitigate damages caused by leaf area reduction due to its influence on cell division. This work was carried out aiming to evaluate the efficiency of side-dressing different rates of nitrogen as a management strategy to maize stem defoliation at different growth stages. The experiment was set in Lages, during the 2008/2009 and 2009/2010 growing seasons. The experimental design was a randomized block with split plots. Three defoliation times were tested in the main plot: eight expanded leaves (V8), fifteen expanded leaves (V15) and tasseling (VT), plus a control without defoliation. Four nitrogen rates were assessed in the split-plots: 0, 50, 100 and 200 kg ha-1 of N. Nitrogen was side-dressed at the defoliation day of each growth stage and at V8 in the control. Defoliations performed at V8 did not reduce grain yield, in comparison to the control, regardless of N rate. Side-dressing N rates at V15 increased grain yield, mitigating damages caused by defoliation. Defoliation carried out at VT promoted great grain yield reduction that could not be alleviated with subsequent nitrogen fertilization. The success of nitrogen side-dress as a strategy to minimize maize grain yield losses caused by defoliation depends on the growth stage leaf area reduction occurs.